Holding the executive accountable: parliament as the beacon of hope to the people - Malapane, A. (My University, 2016)
In recent times, the work of Parliament has been receiving attention on the public domain and discourse. This however does not necessarily mean that it successfully fulfils its mandate to hold the executive accountable. Parliament has been faced with various challenges that have placed doubt in its ability to oversee the executive. Hence, this article examines whether the South African Parliament has a potential and capability to hold the executive to account for its actions or inactions. This is done through inter alia revisiting the systems, procedures, and mechanisms as well as the environment were oversight is performed. In addition, this takes into consideration the theme of Parliament for 2016 which is: “following up on our commitments to the people”. Shija (2012) argues that the true test of a maturing democracy should be determined by the extent of the government’s response to the needs of the people. In this regard, the article argues that Parliament should be the beacon of hope to the people, and be in a position to hold the executive accountable for its activities.
Published in: Journal of Public Administration and Development Alternatives. Vol. 1, No.1, July 2016, 135 - 149
Keywords: Parliament - South Africa